Kualitas Pelayanan Publik Bagi Penyandang Disabilitas Pada Pemerintah Kota Makassar - Herman Herman; Muhammad Irvan Nur Iva; Andi Asripan; Andi Ceri Susilawati; Adelia Ramadani; Ibunga Tang; Nurul Amalia (Perspektif Administrasi Publik dan hukum, 2025)
One of the missions and objectives of establishing an ideal government bureaucracy it to provide good public services to the community, particularly optimal service quality for persons with disabilities. To assess the extent to which the measures/benchmarks of service quality success can be examined from the criteria of the dimensions of public service quality. This study aims to determine the extent to which the quality of public service provided is able to meet the needs of persons with disabilities at the Makassar City Government. This type of research uses a qualitative approach tiwh a case study strategy and both primary and secondary data sources. Data collection is based on observations from the study, and data analysis uses an interactive method that includes data presentation, data condensation, and drawing conclusions. Research results indicate that the quality of public services for people with disabilities at the Makassar City Government specifically sosial service is overall not yet optimal in meeting the needs of people with disabilities and still needs improvement. Based on the service quality dimension indicators, namely: Tangible (physical evidence); Reliability; and Responsiviness, they still need to be enhanced because they are not yet optimal due to limited facilities and infrastructure, lack of employee awareness, and insufficient attention to fulfilling the needs of people with disabilities. Meanwhile, Assurance and Empathy are already categorized as good and adequate thanks to the guidance and quick response from rehabilitation officers. However, comprehensive and continuous improvement is still necessary